2010
DOI: 10.1590/s0102-311x2010001100007
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the validity of a food frequency questionnaire among low-income women in São Paulo, southeastern Brazil

Abstract: This study describes the validity of a food frequency questionnaire (FFQ) in 93 low-income women (20-65 years), participating in a case-control study in São Paulo, Brazil. Two FFQ (FFQ1 and FFQ2, 12 months apart) and three 24-hour dietary recalls (24hR) were conducted between 2003 and 2004 to estimate dietary intake during the past year. The Pearson correlation coefficients (crude, energy-adjusted and de-attenuated) were used for comparisons between FFQ and 24hR. The agreement between the methods was further e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
8
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
2
8
0
2
Order By: Relevance
“…In regards to energy, lower concordance coefficients have been reported in the Willett FFQ (0.16 for women and 0.18 for men) and the Block FFQ (0.37 for women and 0.41 for men) [11] as compared with 0.26 (women) and 0.44 (men) derived from our study. It was particularly noticeable that our correlations for protein were unfavourable, especially in men (0.13), however, our findings were similar to those obtained from a Brazilian cohort (0.20) [45]. For carbohydrate in women, our study yielded a coefficient of 0.38, which compares favourably with the Jackson Heart Study (0.32) [46].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…In regards to energy, lower concordance coefficients have been reported in the Willett FFQ (0.16 for women and 0.18 for men) and the Block FFQ (0.37 for women and 0.41 for men) [11] as compared with 0.26 (women) and 0.44 (men) derived from our study. It was particularly noticeable that our correlations for protein were unfavourable, especially in men (0.13), however, our findings were similar to those obtained from a Brazilian cohort (0.20) [45]. For carbohydrate in women, our study yielded a coefficient of 0.38, which compares favourably with the Jackson Heart Study (0.32) [46].…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, the lower correlation values found in some categories may indicate that the FFQ to some extent systemically over-/under- estimated intake of these nutrients, however, error in over/under estimation by the FFQ is expected. Likewise, Dehghan et al (2012) , Wang et al (2008) , and Cardoso et al (2010) found energy adjustment did not improve the crude correlation in their studies [43-45]. …”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…No que diz respeito à reprodutibilidade do QFA, foram encontrados valores de CCI (0,55-0,83) similares aos observados em outros estudos 21,22 ; da mesma forma, os valores de concordância encontrados nas análises de validade (0,20-0,72) também se mostraram compatíveis com achados de pesquisas semelhantes 21,22,23,24 . Estudos similares apresentam frequentemente valores de coeficiente de correlação entre 0,4 a 0,7, que são considerados como de razoável reprodutibilidade e validade 11 .…”
Section: Discussionunclassified
“…Influence of pylorus preservation procedure that the food intake was over-reported due to limitations inherent to food questionnaires methodologies 18 .…”
Section: Discussionmentioning
confidence: 99%